Last Glacial Maximum and Lateglacial in the Polish High Tatra Mountains - Revised deglaciation chronology based on the 10Be exposure age dating. (1st May 2018) - ,; Arnold, Maurice; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim; Makos, Michał; Rinterknecht, Vincent; Braucher, Régis; Tołoczko-Pasek, Anna
Abstract: Deglaciation chronology of the Polish High Tatra Mountains has been reconstructed based on 10 Be exposure age dating. Fifty-seven rock samples were collected from boulders located on the terminal and lateral moraines that limit the horizontal extent of the LGM and the Lateglacial glaciers in the Biała Woda and Sucha Woda catchments. The uncertainty-weighted mean age of 21.5 ± 2.5 ka obtained for the maximum terminal moraine in the Sucha Woda Valley indicates that the oldest preserved moraines were formed during the global LGM. The age population ranges between 15.1 ± 1.0 and 28.3 ± 2.0 ka, and suggests that glaciers reached their maximum position (LGM I) as early as 28–25 ka and the final stabilization of the form occurred much later possibly after melting of buried dead ice. The younger glacial oscillation (LGM II) occurred no later than 20.5 ka and is represented by well-preserved termino-lateral moraine systems in the Pańszczyca Valley. The first Lateglacial stage (LG1) in the study area is documented in the Rybi Potok Valley at the RP1 moraine (1300 m a.s.l.), which was stable at around 16.6 ± 0.3 ka. The younger LG2 stage has no defined absolute age, however, it is constrained between 16.5 and 15.5 ka by the timing of the LG3 stage. This cold event is represented by well-formed moraines in the Roztoka/Pięć Stawów Polskich, Rybi Potok and Pańszczyca valleys of which exposure age indicates their deposition between 15.0 ± 0.5 and 15.6 ± 0.1 ka. The LG1, LG2 and LG3 stages likely occurred during the Oldest Dryas cold stage (Greenland Stadial 2.1a) related to the North Atlantic cooling Heinrich Event 1. The youngest glacial oscillation is evidenced by moraines in the Pusta and Pańszczyca valleys. These moraines are composed of very large granitic blocks of which exposure ages often exhibit isotope inheritance. This is reflected by the youngest P3 moraine in the Pańszczyca Valley with a mean age of deposition close to the LGM. The R4 moraine system in the Pusta Valley, however, indicates two oscillations phases that occurred at around 13 ka and correlates well with the timing of RP5 moraine formation in the Za Mnichem Valley. The LG4 stage is related to the climate cooling during the Younger Dryas (Greenland Stadial 1). LGM ELAs reconstructed for the Biała Woda and Sucha Woda/Pańszczyca glaciers were located at 1460–1480 m a.s.l. During the Oldest Dryas stages, the ELA in the High Tatras rose from 1600 to 1650 m a.s.l. in the Rybi Potok Valley and from 1700 to 1800 m a.s.l. in the Roztoka/Pięć Stawów Polskich Valley. The Younger Dryas ELA, depending on glacier's exposition, was located between 1950 and 2000 m a.s.l. Climate modelling results show that the LGM glaciers (maximum advance) could have advanced in the High Tatras when the mean annual temperature was lower than today by 11–12 °C and precipitation was reduced by 40–60%. During the Lateglacial stages the temperature decrease in the study area changed from 10 °C during the Oldest Dryas to 6 °C during the Younger Dryas and precipitation lowering decreased from −50% to −30% or even −10%, respectively compare to modern conditions. Highlights: Moraines and bedrock surfaces in the Polish High Tatra Mountains are dated using 10 Be cosmogenic nuclide. We present chronology of the last glaciation in the Sucha Woda and Biała Woda catchments. We present climatic changes in the High Tatra Mountains from the LGM to the Younger Dryas.